2019
DOI: 10.1007/s00339-019-3046-2
|View full text |Cite
|
Sign up to set email alerts
|

Unusual electrical behaviour in sol–gel-synthesised PKMO nano-sized manganite

Abstract: Mixed-valence manganites have gained tremendous attention in the scientific research for its colossal magnetoresistance phenomenon. Nevertheless, the study devoted to praseodymiumbased manganites is still limited to date. The present work aims to investigate the grain size effect on sol-gel grown nano-sized Pr0.85K0.15MnO3 (PKMO). The grain size has been modified by heat treatment ranging from 600 °C to 1000 °C. PKMO samples have been studied in detail to elucidate the correlation of spin, charge, orbital and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Enhancement of LFMR was observed in LSSG and NSSG, as shown in Figure 7a. Moreover, NSSS recorded the highest MR (27.7%) near the TMI and this is attributed to the increase in disordered magnetic spin fluctuations at the high-temperature range [35]. Therefore, we can conclude that NSSS is dominated by intrinsic MR accompanied by weak extrinsic MR. samples at 0.2 and 1 T. The MR of LSMO increases monotonically with the decrease in temperature and it is comparable with the results reported earlier [42,56].…”
Section: Resultsmentioning
confidence: 74%
See 2 more Smart Citations
“…Enhancement of LFMR was observed in LSSG and NSSG, as shown in Figure 7a. Moreover, NSSS recorded the highest MR (27.7%) near the TMI and this is attributed to the increase in disordered magnetic spin fluctuations at the high-temperature range [35]. Therefore, we can conclude that NSSS is dominated by intrinsic MR accompanied by weak extrinsic MR. samples at 0.2 and 1 T. The MR of LSMO increases monotonically with the decrease in temperature and it is comparable with the results reported earlier [42,56].…”
Section: Resultsmentioning
confidence: 74%
“…The grain and crystallite sizes will be increased with the sintering temperature due to the congregation effect [20]. However, single-crystallite grains can be formed when samples are sintered at low temperatures [35] and this was witnessed in our NSSG sample. Furthermore, LSSG was found to have two crystallites in a single grain when referring to the data given in Table 2.…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…In previous work, the effects of grain size on the electrical and magnetic properties of manganites have been reported by many authors. [23][24][25] Dey et al observed a gradual drop of the MIT temperature with a decrease in the grain size, while the ferromagnetic-paramagnetic transition temperature remained almost unchanged in their granular La 0.7 Ca 0.3 MnO 3 samples. [23] Here, we consider the grain size effect to be the reason for the much lower T P in the 6 nm-thick film.…”
Section: Resultsmentioning
confidence: 97%
“…This distortion of MnO6 octahedra leads to the localisation of electrons. In fact, a significant defect in the A-site cations results in a random arrangement of the Mn 3+ and Mn 4+ ions [22,23]. According to the morphology, the average diameter of Pr0.67Ba0.33MnO3 is 2.312 μm by using the scale of 20 μm in Figure 4.…”
Section: Morphology (Microstructural Analysis)mentioning
confidence: 98%